Kamusal yükümlülüklerin işletmeler üzerindeki etkileri - İçten, Orkun (My University, 1997)
The publical obligations that have a great importance for enterprices are responsibilities which states load to economic units to get income. This obligations are responsibilities which enterprices pay but don't know this responsibilities' effects on their organizations The increasing in the publical obligations causes increasing in the profit share of state on the enterprices as a visible partner This case creates the negative effects on the organizational profit. The aim on the finding of the ratio, as an indicator of negative effect of public obligations on the organizations, was the beginning point of the this study. In the final part of the this study, that the enterprice paid %1148 of gross profit as the publical obligations and the share of public obligations in the pluse value produced by enterprice was %53 during a year, were found These ratios indicate that public obligations have a negative effect on source of organizations and there is a transfer of source from enterprice to state. In thise case, The state must not increase publical obligations to get source and at the same time the state must try to include the non-registered enterprices to the tax system. At the otherwise, this case causes unfair competition in fover of the non-registered enterprices in the tax system and the tendency of transformation from tax payer enterprices to the non- registered enterprices in turkish tax system.
Keywords: Bankacılık; İşletmeler; Kamusal Yükümlülükler; Maliye; Vergiler